A high tear material and a method for making the same

CN118186787BActive Publication Date: 2026-10-27FUJIAN AMITY NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410150293.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2026-10-27
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

然而,基布在复合之前需要经过PU溶剂的处理,胶水易过多地渗透到基布中,破坏基布的结构,导致TPU复合材料失去原有的强度和性能,对基布的物性产生一定的破坏

Benefits of technology

[0008]本发明的有益效果在于:本发明的高撕裂材料的制备方法先对基布提前喷水再涂布胶水,可让胶水中架桥剂先和水反应成膜,防止胶水继续渗透到基布中破坏基布物性,从而增加材料的撕裂强力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of fabrics, in particular to a high-tear material and a preparation method thereof. The preparation method comprises the following steps: performing water spraying treatment on one side of a base cloth, scraping glue on the side of the base cloth sprayed with water, completing single-side pasting, and repeating the single-side pasting operation on the other side of the base cloth; drying the pasted base cloth, and then casting a film layer on the surface of the base cloth to obtain the high-tear material; the glue comprises a bridging agent. According to the preparation method, the base cloth is sprayed with water in advance and then coated with glue, the bridging agent in the glue can be reacted with water to form a film in advance, the glue is prevented from continuously penetrating into the base cloth to damage the physical properties of the base cloth, and therefore the tear strength of the material is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fabric technology, specifically to a high tear-resistant material and its preparation method. Background Technology

[0002] TPU composite material is a material made by combining thermoplastic polyurethane (TPU) with a base fabric. The base fabric is usually made of textile materials such as nylon or polyester, which has high strength and abrasion resistance, and can enhance the mechanical properties and durability of the material.

[0003] In the preparation of TPU composite materials, adhesive is needed to bond the base fabric and TPU together to form a whole. For example, Chinese invention patent application number 201810441975.6 discloses a novel fiber composite material with high peel strength and its production method. The TPU film has a PU adhesive layer or a TPU hot melt adhesive layer, and the side with the adhesive layer is bonded to the fiber base fabric to obtain the composite material. However, the base fabric needs to be treated with PU solvent before bonding. Excessive adhesive penetration into the base fabric can damage its structure, causing the TPU composite material to lose its original strength and properties, and causing some damage to the physical properties of the base fabric. Especially at high temperatures, adhesive penetration is more severe, significantly affecting the performance of the base fabric. Conventional production processes use methods such as adjusting the adhesive viscosity to reduce penetration, but this method alone is not very effective, and the tear strength of the base fabric still shows a significant decrease. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a high tear strength material with a base fabric that maintains high tear strength and a method for preparing the same.

[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: a method for preparing a high tear-resistant material, comprising the following steps: spraying water on one side of a base fabric, applying glue to the water-sprayed side of the base fabric to complete single-sided mounting, drying the mounted base fabric, and casting a film layer on the surface of the base fabric to obtain a high tear-resistant material.

[0006] The adhesive contains a crosslinking agent.

[0007] Another technical solution adopted in this invention is: the high tear-resistant material prepared by the above-mentioned high tear-resistant material preparation method.

[0008] The beneficial effects of the present invention are as follows: The method for preparing the high tear strength material of the present invention involves spraying water onto the base fabric before applying adhesive, which allows the crosslinking agent in the adhesive to react with water to form a film, preventing the adhesive from continuing to penetrate into the base fabric and damaging its physical properties, thereby increasing the tear strength of the material. Detailed Implementation

[0009] To explain in detail the technical content, objectives, and effects of the present invention, the following description is provided in conjunction with the embodiments.

[0010] A method for preparing a high tear-resistant material includes the following steps: spraying water on one side of a base fabric, applying adhesive to the water-sprayed side of the base fabric to complete single-sided mounting, drying the mounted base fabric, and casting a film layer on the surface of the base fabric to obtain the high tear-resistant material.

[0011] The adhesive contains a crosslinking agent.

[0012] As can be seen from the above description, the beneficial effects of the present invention are as follows: before applying the adhesive, the surface of the base fabric to be coated is sprayed with water, and then the adhesive containing the crosslinking agent is applied. The crosslinking agent reacts with water to form a thin film structure, making it difficult for the adhesive to penetrate into the base fabric, thereby preventing the physical properties of the base fabric from being damaged by the adhesive and increasing the tear strength of the material.

[0013] Furthermore, the adhesive is a PU (polyurethane) adhesive, which includes the following raw materials in parts by weight: 100 parts PU resin solution, 10-20 parts crosslinking agent and 0-10 parts diluent.

[0014] Preferably, the adhesive comprises the following raw materials in parts by weight: 100 parts PU resin solution, 10-15 parts crosslinking agent, and 3-8 parts diluent.

[0015] As described above, an excessive amount of crosslinking agent will affect the bonding effect of the adhesive; an insufficient amount will reduce the anti-permeability effect. This application adds a slightly sufficient amount of crosslinking agent to allow water to react with the -NCO groups in the crosslinking agent to form a film, while simultaneously ensuring that the crosslinking agent reacts with the PU adhesive to achieve sufficient peel strength. The amount of diluent added in this invention needs to be moderate, allowing it to react with water to form a film while also penetrating a certain proportion into the fabric seams to give the material a certain peel strength.

[0016] Furthermore, the PU resin solution is composed of PU resin and solvent.

[0017] Furthermore, the solvent in the PU resin solution is at least one of butanone, ethyl acetate, dimethyl carbonate, dichloromethane, and dichloroethane.

[0018] Furthermore, the molecular weight of PU resin is ≥100,000.

[0019] Furthermore, the viscosity of the adhesive is ≥80,000 cps.

[0020] As can be seen from the above description, the present invention uses a low-boiling-point solvent to replace conventional high-boiling-point solvents such as DMF (N,N-dimethylformamide) and toluene, which can reduce the processing temperature and thereby improve the strength of the material itself.

[0021] Furthermore, the diluent is one or two of butanone, ethyl acetate, dimethyl carbonate, dichloromethane, and dichloroethane.

[0022] Furthermore, the crosslinking agent is a mixture of MDI (diphenylmethane diisocyanate) and TDI (toluene diisocyanate).

[0023] As can be seen from the above description, the isocyanate groups of MDI and TDI are prone to forming a network structure with the best peel strength.

[0024] Furthermore, the mass of TDI in the crosslinking agent is greater than the mass of MDI.

[0025] As can be seen from the above description, MDI is prone to freezing at low temperatures. In order to reduce freezing, the mass of TDI in the crosslinking agent should be greater than the mass of MDI.

[0026] Furthermore, the water spray volume during water spraying treatment is 5–100 gsm.

[0027] Preferably, the water spray volume during water spraying is 20–40 gsm.

[0028] As can be seen from the above description, if the water spray volume is too large, the moisture will not be completely dried, which will affect the peel strength of the material; if the water spray volume is too small, the anti-penetration effect will be reduced. Therefore, the water spray volume during water spraying treatment should be controlled at 5-100 gsm.

[0029] Furthermore, the coating temperature for single-sided mounting is 100–110℃, the coating speed is 10–20 m / min, and the adhesive weight is 10–30 gsm.

[0030] As described above, after lamination, excess moisture and solvent are dried to prevent excess moisture from affecting the peel strength of subsequent materials. Simultaneously, this invention employs lower coating and drying temperatures to prevent high temperatures from damaging the base fabric properties and to prevent severe adhesive penetration at high temperatures.

[0031] Furthermore, preheating is required before casting, with a preheating temperature of 110–120°C.

[0032] Furthermore, the temperature during casting is 200–210℃, and the speed is 10–17 m / min.

[0033] Preferably, the temperature during casting is 200–205°C and the speed is 10–12 m / min.

[0034] As described above, increasing the casting temperature allows the adhesive to activate more quickly and form an interaction force with the film layer, thus strengthening the peel strength; increasing the speed reduces the heat of the film, achieving the effect of increasing the temperature. During casting, the contact time between the base fabric and the high-temperature melt is very short, only 1-3 seconds, at which point the high temperature has little impact on adhesive penetration.

[0035] Another technical solution adopted in this invention is: the high tear-resistant material prepared by the above-mentioned high tear-resistant material preparation method.

[0036] Embodiment 1 of the present invention is: a method for preparing a high tear-resistant material, comprising the following steps:

[0037] S1: Spray water on one side of the base fabric, then apply PU adhesive to the water-sprayed side of the base fabric using a scraper. The scraping temperature is 105℃, the scraping speed is 15m / min, and the adhesive weight is 20gsm. This completes the single-sided mounting.

[0038] The adhesive has a viscosity of 100,000 cps and is made by mixing 100g of PU resin solution, 17g of crosslinking agent and 5g of diluent. The PU resin solution is made by mixing 100g of PU resin and 5g of methyl ethyl ketone (MEK) and the molecular weight of the PU resin is 120,000. The diluent is ethyl acetate. The crosslinking agent is a mixture of MDI and TDI with a mass ratio of 1:2.

[0039] S2: Place the laminated base fabric into an oven for drying. The oven temperature is 105℃ and the drying speed is 5m / min.

[0040] S3: The dried base fabric is preheated at 115°C, and then a film layer is cast on the surface of the base fabric at a temperature of 203°C and a speed of 11m / min to obtain a high tear-resistant material.

[0041] The film layer is formed by melting 100g of TPU (thermoplastic polyurethane elastomer rubber), 5g of color masterbatch, and 2g of additives; the TPU is HF-4390A-1 from Zhejiang Huafeng Thermoplastic Polyurethane Co., Ltd.; the color masterbatch consists of TPU, color powder, and dispersant in a mass ratio of 100:25:1; the additives consist of UV stabilizer, antioxidant, and antibacterial agent in a mass ratio of 1:1:1. The dispersant is PE520 from Clariant Chemicals (China) Co., Ltd., the UV stabilizer is UV234 from BASF AG, the antioxidant is antioxidant 1010, and the antibacterial agent is SilverShief IB10 from Microban (USA).

[0042] Embodiment 2 of the present invention is: a method for preparing a high tear-resistant material, comprising the following steps:

[0043] S1: Spray water onto one side of the base fabric, then apply PU adhesive to the water-sprayed side of the base fabric using a scraper. The scraping temperature is 100℃, the scraping speed is 10m / min, and the adhesive weight is 10gsm. This completes the single-sided mounting.

[0044] The adhesive has a viscosity of 80,000 cps and is composed of 100g of PU resin solution and 10g of crosslinking agent. The PU resin solution is prepared by mixing 100g of PU resin and 1-10g of solvent. The PU resin has a molecular weight of 100,000. The solvent is a mixture of ethyl acetate and dimethyl carbonate in a 1:1 volume ratio. The diluent is a mixture of butanone and dimethyl carbonate in a 1:1 volume ratio. The crosslinking agent is a mixture of MDI and TDI in a 1:3 mass ratio.

[0045] S2: Place the laminated base fabric into an oven for drying. The oven temperature is 100℃ and the drying speed is 3m / min.

[0046] S3: The dried base fabric is preheated at 110°C, and then a film layer is cast on the surface of the base fabric at a temperature of 200°C and a speed of 10m / min to obtain a high tear-resistant material.

[0047] The film layer is melted from 100g of TPU (thermoplastic polyurethane elastomer rubber), 0.5g of color masterbatch, and 0.1g of additives. The TPU is HF-4390A-1 manufactured by Huafeng. The color masterbatch consists of TPU, color powder, and dispersant in a mass ratio of 100:25:1. The additives consist of UV stabilizer, antioxidant, and antibacterial agent in a mass ratio of 1:1:1. The dispersant is PE520 from Clariant Chemicals (China) Co., Ltd., the UV stabilizer is UV234 from BASF AG, the antioxidant is antioxidant 1010, and the antibacterial agent is SilverShief IB10 from Microban (USA).

[0048] Embodiment 3 of the present invention is: a method for preparing a high tear-resistant material, comprising the following steps:

[0049] S1: Spray water onto one side of the base fabric, then apply PU adhesive to the water-sprayed side of the base fabric using a scraper. The scraping temperature is 110℃, the scraping speed is 20m / min, and the adhesive weight is 30gsm. This completes the single-sided mounting.

[0050] The adhesive has a viscosity of 110,000 cps and is made by mixing 100g of PU resin solution, 20g of crosslinking agent, and 10g of diluent. The PU resin solution is made by mixing 100g of PU resin and 1-10g of solvent. The PU resin has a molecular weight of 120,000. The solvent is a mixture of dichloromethane and dichloroethane in a 1:1 volume ratio. The diluent is a mixture of dichloromethane and dichloroethane in a 1:1 volume ratio. The crosslinking agent is a mixture of MDI and TDI in a 1:2 mass ratio.

[0051] S2: Place the laminated base fabric into an oven for drying. The oven temperature is 110℃ and the drying speed is 10m / min.

[0052] S3: The dried base fabric is preheated at 120°C, and then a film layer is cast on the surface of the base fabric at a temperature of 210°C and a speed of 17m / min to obtain a high tear-resistant material.

[0053] The film layer is melted from 100g TPU (thermoplastic polyurethane elastomer rubber), 10g color masterbatch, and 5g additives. The TPU is HF-4390A-1 manufactured by Huafeng. The color masterbatch consists of TPU, color powder, and dispersant in a mass ratio of 100:25:1. The additives consist of UV stabilizer, antioxidant, and antibacterial agent in a mass ratio of 1:1:1. The dispersant is PE520 from Clariant Chemicals (China) Co., Ltd., the UV stabilizer is UV234 from BASF AG, the antioxidant is antioxidant 1010, and the antibacterial agent is SilverShief IB10 from Microban (USA).

[0054] Example 4 of the present invention is a high tear-resistant material prepared by the preparation method of Example 1.

[0055] Comparative Example 1 of the present invention is:

[0056] The only difference between Comparative Example 1 and Example 1 is that the PU adhesive is applied directly without spraying water.

[0057] Comparative Example 2 of the present invention is as follows:

[0058] The only difference between Comparative Example 2 and Example 1 is that the preheating temperature in S3 is 65°C, the temperature during casting is 175°C, and the speed is 3.5 m / min.

[0059] The tear performance and peel strength of the materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested, and the test results are shown in Table 1.

[0060] Table 1

[0061]

[0062] Comparing Example 1 with Comparative Example 1, it can be seen that water spraying reduces the peel strength of the material while greatly increasing its tear strength. Comparing Example 1 with Comparative Example 2, it can be seen that using higher temperature and speed during casting can improve the peel strength and tear strength of the material.

[0063] In summary, the method for preparing high-tear-strength materials provided by this invention utilizes a high-viscosity adhesive, a low-boiling-point solvent, and sprays water onto the surface of the substrate to be coated. This allows the adhesive containing the crosslinking agent to react with water to form a thin film structure, thereby reducing adhesive penetration into the substrate and preventing damage to the substrate's properties by the adhesive, thus increasing the material's tear strength. Simultaneously, increasing the casting temperature and speed allows the adhesive to be activated more quickly and interact with the film layer, further enhancing peel strength.

[0064] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent modifications made using the present invention specification, or direct or indirect applications in related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing a high-tear-resistance material, characterized in that, Includes the following steps: One side of the base fabric is sprayed with water, and glue is scraped onto the water-sprayed side of the base fabric to complete the single-sided mounting. After the mounted base fabric is dried, a film layer is cast on the surface of the base fabric to obtain a high tear-resistant material. The adhesive includes a crosslinking agent, and the viscosity of the adhesive is greater than or equal to 80,000 cps; The water spray volume during the water spraying treatment is 5~100gsm; The coating temperature for single-sided mounting is 100~110℃, the coating speed is 10~20m / min, and the adhesive weight is 10~30gsm.

2. The method for preparing the high tear-resistant material according to claim 1, characterized in that, The adhesive is a PU adhesive, which includes the following raw materials in parts by weight: 100 parts PU resin solution, 10-20 parts crosslinking agent and 0-10 parts diluent.

3. The method for preparing the high tear-resistant material according to claim 2, characterized in that, The solvent in the PU resin solution is at least one of butanone, ethyl acetate, dimethyl carbonate, dichloromethane, and dichloroethane.

4. The method for preparing the high tear-resistant material according to claim 2, characterized in that, The diluent is one or two of butanone, ethyl acetate, dimethyl carbonate, dichloromethane, and dichloroethane.

5. The method for preparing the high tear-resistant material according to claim 2, characterized in that, The crosslinking agent is a mixture of MDI and TDI.

6. The method for preparing the high tear-resistant material according to claim 1, characterized in that, The drying temperature is 100~110℃.

7. The method for preparing the high tear-resistant material according to claim 1, characterized in that, The casting process requires preheating at a temperature of 110-120°C.

8. The method for preparing the high tear-resistant material according to claim 1, characterized in that, The temperature during the casting process is 200~210℃, and the speed is 10~17m / min.

9. A high-tear-resistance material prepared by any of the high-tear-resistance material preparation methods described in claims 1-8.

Citation Information

Patent Citations

  • A fiber composite material with high peel strength and its production method

    CN108790333B

  • Modified TPU film fabric compound and preparation method thereof

    CN108274864A

  • Preparation method of high-tear impermeable material

    CN118493961A

  • Preparation method of composite material for hyperbaric oxygen chamber

    CN118927655A